Alterations of functional connectivity between thalamus and cortex before and after decompression in cervical spondylotic myelopathy patients: a resting-state functional MRI study. Issue 5 (25th March 2020) - Peng, Xinji; Tan, Yongming; He, Laichang; Ou, Yangtao
Abstract : Objective: Cervical spondylotic myelopathy is regarded as a chronic, special incomplete spinal cord injury, so the sensory components transmitted to thalamus decreased after distal spinal cord injury, which lead the disturbance of thalamus-cortex circuits, which might explain the alterations of clinical function of cervical spondylotic myelopathy patients. However, for lack of effective methods to evaluate the disturbance circuits and how the relative mechanism adapt to the recovery of cervical spondylotic myelopathy patients after decompression. Therefore, this study aim to explore how the possible mechanism of thalamus-cortex circuits reorganization adapt to the recovery of clinical function. Methods: Regard thalamus as the interest area, we evaluate the brain functional connectivity within 43 pre-operative cervical spondylotic myelopathy patients, 21 post-operative (after 3 months) cervical spondylotic myelopathy patients and 43 healthy controls. Functional connectivity difference between pre-/post-operative cervical spondylotic myelopathy group and healthy controls group were obtained by two independent samples t -test, and difference between pre-operative cervical spondylotic myelopathy and post-operative cervical spondylotic myelopathy group were obtained by paired t -test. Clinical function was measured via Neck Disability Index and Japanese Orthopaedic Association scores. Furthermore, Pearson correlation were used to analyse the correlation between functional connectivity values and clinical scores. Results: Compared with healthy controls group, pre-operative cervical spondylotic myelopathy group showed increased functional connectivity between left thalamus and bilateral lingual gyrus/cuneus/right cerebellum posterior lobe (Voxel P -value <0.01, Cluster P -value <0.05, GRF corrected); post-operative cervical spondylotic myelopathy group manifested decreased functional connectivity between right thalamus and bilateral paracentral lobe/precentral gyrus but significantly increased between right thalamus and pons/superior temporal gyrus. In comparison with pre-operative cervical spondylotic myelopathy group, post-operative cervical spondylotic myelopathy group showed increased functional connectivity between bilateral thalamus and posterior cingulate lobe, angular gyrus, medial prefrontal, but significantly decreased functional connectivity between bilateral thalamus and paracentral lobe/precentral gyrus. The functional connectivity between left thalamus and bilateral lingual gyrus/cuneus/right cerebellum posterior lobe in pre-operative cervical spondylotic myelopathy group have a significantly positive correlation with sensory Japanese Orthopaedic Association scores ( r = 0.568, P < 0.001). The functional connectivity between thalamus and paracentral lobe/precentral gyrus in post-operative cervical spondylotic myelopathy group have a significantly positive correlation with upper limb movement Japanese Orthopaedic Association scores ( r = 0.448, P = 0.042). Conclusion: Pre- or post-operative cervical spondylotic myelopathy patients showed functional connectivity alteration between thalamus and cortex, which suggest adaptive changes may favor the preservation of cortical sensorimotor networks before and after cervical cord decompression, and supply the improvement of clinical function.